JefiPIC: A 3-D Full Electromagnetic Particle-in-Cell Simulator Based on Jefimenko’s Equations on GPU (Communications in Computational Physics, 2024)
This paper presents a novel 3-D full electromagnetic particle-in-cell (PIC)code called JefiPIC, which uses Jefimenko’s equations as the electromagnetic (EM) fieldsolver through a full-space integration method. Leveraging the power of state-of-the-art graphic processing units (GPUs), we have made the challenging integral task ofPIC simulations achievable. Our proposed code offers several advantages by utilizing the integral method. Firstly, it offers a natural solution for modeling non-neutralplasmas without the need for pre-processing such as solving Poisson’s equation. Secondly, it eliminates the requirement for designing elaborate boundary layers to absorbfields and particles. Thirdly, it maintains the stability of the plasma simulation regardless of the time step chosen. Lastly, it does not require strict charge-conservationparticle-to-grid apportionment techniques or electric field divergence amendment algorithms, which are commonly used in finite-difference time-domain (FDTD)-basedPIC simulations. To validate the accuracy and advantages of our code, we comparedthe evolutions of particles and fields in different plasma systems simulated by threeother codes. Our results demonstrate that the combination of Jefimenko’s equationsand the PIC method can produce accurate particle distributions and EM fields in open-boundary plasma systems. Additionally, our code is able to accomplish these computations within an acceptable execution time. This study highlights the effectivenessand efficiency of JefiPIC, showing its potential for advancing plasma simulations.
Keywords: Particle-in-cell; Jefimenko’s equation; plasma simulation; integral method; GPU.